IN VITRO ANTIFUNGAL ACTIVITY AND CYTOTOXICITY SCREENING OF DRY CRUDE EXTRACTS FROM BRAZILIAN AMAZONIA PLANTS - Soares, Mônica Regina Pereira Senra; Caneschi, César Augusto; Chaves, Maria das Graças Afonso Miranda; Mota, Marcela; Stroppa, Pedro Henrique Fazza; Barbosa, Wagner; Raposo, Nádia Rezende Barbosa (African Journal of Traditional, Complementary and Alternative Medicines, 2018)
Background: Antifungal multidrug resistance has been reported worldwide and has stimulated investigations of plant species for the treatment of candidiasis. In particular, in vitro antifungal activities and cytotoxicity of dry extracts from Ceasalpinia ferrea (tul.) Martius, Brosimum acutifolium Huber, and Salacia impressifolia (Miers) A.C. Smith were evaluated. Materials and Methods: Minimum inhibitory concentrations (MIC) and minimum fungicide (MFC) values were established according to the protocol M27-A2 of the Clinical and Laboratory Standards Institute (CLSI). Subsequent evaluations were performed using strains of Candida albicans from the American Type Culture Collection (ATCC) 10231, clinical isolated Candida albicans, Candida glabrata (CCT) 0728, Candida krusei (FTI) CCT 1517, and Candida guilliermondii (CCT) 1890. Morphological changes were evaluated using scanning electron microscopy (SEM), and cytotoxicity was evaluated in murine L929 fibroblast cells after treatment with plant extracts. Results: MIC values indicated antifungal potential of all three extracts against the main fungi that causes candidiasis. Conclusion: In particular, C. ferrea showed promising antimicrobial potential against all strains. Hence, future studies are warranted to investigate pharmacologically active compounds from this extract that could be used as prototypes for drug development and/or as a source of raw pharmaceutical materials for the treatment of candidiasis.